Cultural Discontinuity and Search for Indentity: The case of Post-communist Croatia - Spajić-Vrkaš, Vedrana (Array, 1997)
The aim of the paper was to apply anthropological concepts of cultural discontinuity, oppositional identity and oppositional frame of reference to the analysis of the post-communist formation of Croatian cultural identity. It has been shown that the issue of nationness and state-ness not only represent the most important structural elements of the contemporary Croatian cultural identity but make a basis of its dualism. Short review of the 20th Century changes leads to the conclusion that contemporary identity oppositions are in relation to earlier cultural discontinuities during which Croatian culture and Croatian cause were suppressed of forcefully subordinated to other causes. These discontinuities produced oppositional frames of references and oppositional identities which were directed both outwardly and inwardly and which, as such, outlived the 1990 changes when Croatia became an independent state. Today, internal bipolarity determine the content and context of the post-communist formation of Croatian cultural identity in matters of language, history, cultural symbols and dominant cultural values. These oppositional voices (re)create not only social and cultural boundaries and hierarchies but oppositional croatian worlds in which negotiation and dialogue have the role of mere rhetoric.